Race, racism and mnemonic freedom in the digital afterlife. Issue 5 (4th April 2021) - Recuber, Timothy
ABSTRACT: American public discourse is increasingly populated by the names of Black men and women killed by police, often because their deaths were caught on camera and footage of their deaths has circulated virally online. In this way they are doubly victimized, losing not only their lives but also the agency to define themselves and the ways they'd like to be remembered. At the same time, the lives of many Black victims of police violence have been commemorated using digital platforms, especially hashtags on Twitter. So what exactly does it mean to be remembered online in these contexts? To help answer this question, this article is built around a discourse analysis of 990 tweets from two such hashtags: #IfTheyGunnedMeDown and #IfIDieInPoliceCustody. In addition to pushing back against racist stereotypes and state violence, I argue that these two hashtags collect the digital claims to mnemonic freedom of thousands of Black people. The term mnemonic freedom, as I use it here, refers to the ability to ensure that the stories we tell about ourselves, and the morals and meanings of our lives, get remembered by others in the ways that we want. But more than simply that, these hashtags show how mnemonic freedom might be achieved collectively rather than individually.